The impact of tourism village on the community’s economy of Setanggor village in Lombok Island, Indonesia - Tutik Sukmalasari Putri; Agus Mahmud; Muhammad Muhajir Aminy (Journal of Enterprise and Development (JED), 2022)
Purpose — To ascertain the development strategy used to establish tourism communities and the economic impact on the community.Research method — This study employs a qualitative approach with interview as the data collection method which is sourced from the head of the tourism awareness group (POKDARWIS) and tourism business actors, including songket artisans, guiders, small traders, breeders, employees of tourist attractions, lodging services, art studios, travel services, compass fertilizer businesses, village heads, and the community.Result — The study's findings include the development model that was used to develop Setanggor Tourism Village, namely the Community Based Tourism development model which entails three components: community participation in decision-making, community involvement in businesses and profit generation, and resource empowerment and profit distribution. The growth of this tourism village has a significant impact on people's income, employment possibilities, prices, community ownership and control, and tourism objects.